The Soundest Investment of All - Ingersoll, C. Jared (Tufts Archival Research Center, 2006)
C. Jared Ingersoll, Director of the Pennsylvania Railway, describes the tragic loss of his wife and son and how he persevered through tragedy to find happiness in life again as a result of his faith and belief in an afterlife and the value and enjoyment he finds from being kind and generous. This episode is a rebroadcast of an earlier airing.